AUTOMATED SYNTHESIS OF ASPHERICAL OPTICAL SYSTEMS FOR ULTRA-WIDE INFRARED LENSES - SOKURENKO, VYACHESLAV; VOLOSCHUK, BOHDAN; SOKURENKO, OLEG (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This study evaluates the effectiveness of the automated synthesis technique for aspheric optical systems of fast ultra-wide-angle infrared lenses. The synthesis is performed with one of modern stochastic global optimization algorithms. The designed two four-lens systems are practically corrected for theta distortion. They contain second-order aspheric surfaces and are designed of different lens materials. In the first optical system, all lenses are made of germanium. In another optical system, the material of the second lens is zinc selenide, and while other lenses are germanium. Zinc selenide has been used to test the potential for additional correction of chromatic aberrations. The systems have a focal length of 3.8 mm, a relative aperture of 1:1 and a field of view angle of 150°. Taking into account the distortion of real rays, the actual diameter of the image circle for both systems is 9.8 mm, which ensures compatibility with microbolometric sensors with 640×480 and 640×512 pixels having the size of 12 μm. When using a computer with an Intel Core i7 processor operating in multi-threaded mode, and optimizing the values ​​of the polychromatic modulation transfer function, which requires intensive Fourier transform calculations, the optical design process of such systems can take up to 3 hours. For synthesized optical systems, the values ​​of polychromatic diffraction modulation transfer functions determined for the Nyquist spatial frequency of 41.7 lines/mm exceed 0.22 for all given points and exceeds 0.42 on the axis. Applying zinc selenide in the second lens helped to improve the image quality at the periphery Analysis of the results showed that the proposed approach enables to achieve automated correction of monochromatic and chromatic aberrations and provides high-quality optical characteristics of fast lenses for the long-wave infrared spectrum.
Keywords: ultra-wide-angle lens; infrared; medical thermal imagers; modulation transfer function; microbolometric sensor